Empowering Small and Medium-Sized Knowledge-Based Companies Using Digital Entrepreneurship Development - Melika Fard; Mohammad Reza Kabaranzad Ghadim; Jalal Haghighat Monfared (مطالعات مدیریت کسب و کار هوشمند, 2021)
In recent years, information and communication technology has come to the aid of entrepreneurship and a new debate called digital entrepreneurship has emerged. The purpose of this study is to present a conceptual model of digital entrepreneurship development in small and medium knowledge based companies.  After reviewing literature and interviewing with 17 experts in universities and organizations digital entrepreneurship developmental factors were presented that were 147 codes. Using content analysis and focus group methods, these codes were grouped into 29 based content and 7 organizer contents. In the next step, using interpretative structural modeling method, the modeling of the basic themes and the organizing content created and the final model of digital entrepreneurship development in SME knowledge-based companies has been made in three level of contextual, structural and content factors. The results showed that the contextual factors with the most impact and structural factors with the most impressionability, have an important role in the development of digital entrepreneurship in SME knowledge-based companies.